Quasi-static modelling of compliant mechanisms: application to a 2-DOF underactuated finger - C. Quennouelle; C. Gosselin (Mechanical Sciences, 2011)
In this paper, the kinematostatic and the quasi-static models of parallel mechanisms are applied to underactuated mechanisms. Both models are extended to the cases for which the actuated joints are not kinematically independent, and for which the external loads are function of the configuration of the mechanism, the grasped object being considered as not perfectly rigid. An application to a 2-DOF underactuated compliant finger is then presented with details about the implementation of the kinematostatic and the quasi-static models. Finally, some numerical results are given that illustrate possible contributions of these models for the analysis and the control of underactuated mechanisms. This paper was presented at the IFToMM/ASME International Workshop on Underactuated Grasping (UG2010), 19 August 2010, Montréal, Canada.